The Association of Childhood Maltreatment With Lipid Peroxidation and DNA Damage in Postpartum Women - Boeck, Christina; Gumpp, Anja M.; Koenig, Alexandra M.; Radermacher, Peter; Karabatsiakis, Alexander; Kolassa, Iris-Tatjana (Frontiers in Psychiatry, 2019)
Childhood maltreatment (CM) is associated with an increased risk for the development of psychiatric and somatic disorders in later life. A potential link could be oxidative stress, which is defined as the imbalance been the amount of reactive oxygen species (ROS) and the neutralizing capacity of anti-oxidative defense systems. However, the findings linking CM with oxidative stress have been inconsistent so far. In this study, we therefore aimed to further explore this association by investigating biological markers of DNA and lipid damage due to oxidation in a comprehensive approach over two study cohorts of postpartum women (study cohort I and study cohort II). The severity of CM experiences (maltreatment load) was assessed in both studies using the Childhood Trauma Questionnaire. In study cohort I (N = 30), we investigated whether CM was associated with higher levels of structural DNA damage in peripheral blood mononuclear cells (PBMC) by two methods that are highly sensitive for detecting nuclear DNA strand breaks (comet assay and γH2AX staining). In study cohort II (N = 118), we then assessed in a larger cohort, that was specifically controlled for potential confounders for oxidative stress measurements, two established serum and plasma biomarkers of oxidative stress, one representing oxidative DNA and RNA damage (8-hydroxy-2'-deoxyguanosine and 8-hydroxyguanosine; 8-OH(d)G) and the other representing lipid peroxidation (8-isoprostane). In study cohort I, the analyses revealed no significant main effects of maltreatment load on cellular measures of nuclear DNA damage. The analyses of peripheral oxidative stress biomarkers in study cohort II revealed a significant main effect of maltreatment load on free 8-isoprostane plasma levels, but not on total 8-isprostane plasma levels and 8-OH(d)G serum levels. Taken together, by combining different methods and two study cohorts, we found no indications for higher oxidative DNA damages with higher maltreatment load in postpartum women. Further research is needed to investigate whether this increase in free 8-isoprostane is a marker for oxidative stress or whether it is instead functionally involved in ROS-related signaling pathways that potentially regulate inflammatory processes following a history of CM.